2018
DOI: 10.1080/10715762.2018.1475732
|View full text |Cite
|
Sign up to set email alerts
|

Dunnione protects against experimental cisplatin-induced nephrotoxicity by modulating NQO1 and NAD+ levels

Abstract: Despite being an efficacious anticancer agent, the clinical utility of cisplatin is hindered by its cardinal side effects. This investigation aimed to appraise potential protective impact of dunnione, a natural naphthoquinone pigment with established NQO1 stimulatory effects, on cisplatin nephrotoxicity of rats. Dunnione was administered orally at 10 and 20 mg/kg doses for 4 d and a single injection of cisplatin was delivered at the second day. Renal histopathology, inflammatory/oxidative stress/apoptotic mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…Interestingly, Cis decreased the molecular antioxidant defense system, as evidenced by the significant downregulation of renal NRF2, cytoglobin, CREB, SIRT1, and PPAR‐γ expressions along with FOXO‐3 upregulation. These results are in agreement with previous studies done by Cao et al [ 58 ] and Nassari Soltan Ahmad et al [ 59 ] On the contrary, UMB treatment resulted in a significant upregulation of NRF2 and cytoglobin proteins as well as an effective increase in the expression of NRF2, CREB, SIRT1, and PPAR‐γ genes along with FOXO‐3 downregulation. Our previous work showed that UMB attenuated oxidative injury and enhanced oxidant/antioxidant status in the methotrexate‐induced nephrotoxicity model, [ 29 ] supporting the role of UMB in attenuation of ROS injury.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, Cis decreased the molecular antioxidant defense system, as evidenced by the significant downregulation of renal NRF2, cytoglobin, CREB, SIRT1, and PPAR‐γ expressions along with FOXO‐3 upregulation. These results are in agreement with previous studies done by Cao et al [ 58 ] and Nassari Soltan Ahmad et al [ 59 ] On the contrary, UMB treatment resulted in a significant upregulation of NRF2 and cytoglobin proteins as well as an effective increase in the expression of NRF2, CREB, SIRT1, and PPAR‐γ genes along with FOXO‐3 downregulation. Our previous work showed that UMB attenuated oxidative injury and enhanced oxidant/antioxidant status in the methotrexate‐induced nephrotoxicity model, [ 29 ] supporting the role of UMB in attenuation of ROS injury.…”
Section: Discussionsupporting
confidence: 93%
“…In favour of these findings, it has been demonstrated that dunnione, a natural quinone with extensive structural analogies to B-LAP, elevates nuclear presence of Nrf2 and simultaneously up-regulates the expressions of HO-1 and NQO1 in the kidneys of cisplatin nephrotoxic rats. 28 Additionally, Wang et al 29 showed that the activation of SIRT/LKB1/AMPK signalling pathway protects H9c2 cells, adult mice cardiomyocytes and 129S1/ SyImJ mice against DOX-induced cardiotoxicity through anti-oxidative, anti-apoptotic and anti-inflammatory actions. Moreover, it was reported that DOX-induced cardiotoxicity can be reversed by activation of Sirt1/AMPK/Nrf2 pathway by suppression of intracellular oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, B‐LAP, apart from modulating the inflammatory markers IL‐1β and TNF‐α, elevated nuclear accumulation of Nrf2 in cardiac tissues of DOX‐treated mice and enhanced both the gene expression and protein levels of HO‐1, as well as GST; it, additionally, up‐regulated the gene expression of NQO‐1 and cardiac activities of GPX, SOD and CAT, leading to diminished levels of MDA. In favour of these findings, it has been demonstrated that dunnione, a natural quinone with extensive structural analogies to B‐LAP, elevates nuclear presence of Nrf2 and simultaneously up‐regulates the expressions of HO‐1 and NQO1 in the kidneys of cisplatin nephrotoxic rats . Additionally, Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Targeting NAD + redox balance has been suggested as a strategy for fighting cisplatin-induced kidney injury [ 18 , 60 ]. Therefore, there has been an increasing interest in studying redox biochemistry and NAD + redox signaling in the pathogenesis of cisplatin renal toxicity [ 32 , 61 , 62 , 63 , 64 ]. The major NAD + -dependent redox enzymes that may be involved in cisplatin-induced kidney injury are shown in Figure 4 .…”
Section: Effects Of Cisplatin On Major Individual Nad + ...mentioning
confidence: 99%